A EVALUASI PROGRAM SOCIAL EMOTIONAL LEARNING DALAM MENGATASI KASUS BULLYING DI SMP NEGERI SIDOHARJO KABUPATEN MUSI RAWAS: Social Emotional Learning, Bullying - Echa Sriyanti; Putri Kartiwi , Asti (Manajer Pendididikan, 2025)
The purpose of this study was to analyse the evaluation of the Social Emotional Learning program in overcoming bullying cases at SMP Negeri Sidoharjo, Musi Rawas Regency. This research uses descriptive quantitative research. The population in this study were students of SMP Negeri Sidoharjo, Musi Rawas Regency. The sampling technique was carried out using purposive sampling technique, the sample of this study was 78 people. Data collection techniques using a questionnaire. Data analysis techniques using Ideal and Standard deviation ideal. The results of this study 1) Context evaluation of SEL programme in Sidoharjo State Junior High School shows that this programme has the potential to reduce bullying cases.2) Evaluation of SEL programme inputs is essential to identify the strengths and weaknesses of the programme. By understanding the existing inputs, schools can make improvements and enhancements to ensure the SEL programme runs effectively in addressing bullying issues. 3) The process evaluation of the SEL programme provides a clearer picture of how the programme works on the ground. 4) Product evaluation of SEL programmes is essential to measure the long-term impact of the programme.